ANALISIS FUNDAMENTAL MAKRO, PENGELOLAAN MODAL KERJA, DAN PENGENDALIAN BIAYA TERHADAP KINERJA KEUANGAN DENGAN FINANCIAL TECHNOLOGY DAN MANAJEMEN LABA SEBAGAI VARIABEL INTERVENING PADA PT BANK JATIM TBK TAHUN 2019-2023 - Kayla Dedyanti, Mayrilin; Hwihanus, Hwihanus (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2025)
The purpose of this study is to analyze macro fundamentals, working capital management, cost control with financial technology and earnings management as intervening variables on the financial performance of PT Bank Jatim Tbk during the 2019-2023 period. The selection of this topic is based on the importance of understanding the factors that can improve the company's financial performance, especially in the face of macroeconomic challenges and the rapid development of financial technology. This research uses quantitative methods and statistical analysis to reveal the relationship between existing variables. The analytical tool used is SmartPLS, which allows researchers to test the structural relationships between variables in the model that has been developed. This study also identified several limitations, including the limited data used, only one company, and a focus on a limited time period between 2019 and 2023. The research shows that macro fundamentals have a significant impact on financial performance, financial technology, and earnings management. In addition, working capital management and cost control also proved to have a significant effect on financial performance and financial technology. However, no significant effect was found between financial technology and financial performance directly. This shows that although financial technology is growing rapidly, its implementation at PT Bank Jatim Tbk is not yet fully implemented.